Antibacterial activity of essential oils of Salvia Officinalis growing in Morocco - Youssef Lahlou; Sara Moujabbir; Abdelghani Aboukhalaf; Belkassem El Amraoui; Toufiq Bamhaoud (National Institute of Public Health - National Institute of Hygiene, 2023)
ackground. The bacterial infections treatment is complicated by antibiotic resistance. In this fact, the need for new therapeutic approaches to control bacterial infections is crucial. Therefore, discovering new antibiotics from medicinal plants, able to kill drug-resistant bacteria, is essential to saving modern medicine. Objective. This study was to evaluate the in vitro antibacterial activity of Salvia officinalis essential oil (SoEO) growing in Morocco. Material and methods. The essential oil was extracted by hydro distillation, minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) were determined by agar dilution method. The essential oil was analyzed by Fourier-transform infrared spectroscopy (FTIR) and fractionated/purified using column chromatography followed by thin-layer chromatography (TLC). Results. The results revealed that SoEO showed higher antimicrobial activity against Enterococcus faecalis and Citrobacter freundii. Fourier-transform infrared spectroscopy (FTIR) analysis, and purification/fractionation of SoEO, indicates that the most polar fraction F6 is the active fraction of SoEO. This finding can be explained by the existence of polar compounds in this fraction including alcohols, and phenols as thymol, eugenol, globulol, and spathulenol. Conclusions. It can be conclude that alcohols and phenols from Salvia officinalis essential oil (SoEO) have promising antibacterial activity. This action can offer a great possibility of the application of SoEO in the treatment of bacterial diseases.